PENGABDIAN KEPADA MASYARAKAT MELALUI PROGRAM KULIAH KERJA NYATA STAI DARUL FALAH DI DESA CICANGKANGGIRANG BANDUNG BARAT - Fikri Rizkia Muhammad; Ayu Puji Rahayu; Hevie Setia Gunawan (LPPM STAI Darul Falah, 2023)
Real Work Lecture, Kuliah Kerja Nyata (KKN) is a tangible manifestation in implementing the Tri Dharma of Higher Education, one of which is community service where students must devote themselves wholeheartedly which is carried out with an approach in the community. This KKN is the task of universities to determine the regions and groupings determined by LP2M, the benefits of which are to introduce aspects of education, health and social society. With the KKN in Cicangkanggirang village, it is hoped that students will be able to optimize the form of kinship, good character and students are able to face problems that occur during times of crisis and are independent and able to think critically in facing challenges in real life. A program that has been successfully implemented includes in the field of education such as tutoring, smart homes, seminars and regular recitations. In the health sector, such as posyandu, blood donation and environmental hygiene and in the social sector, such as village administration services, distribution of BLT, donations to orphans, celebrating the Republic of Indonesia's Independence Day, Tabligh akbar and helping UMKM. The obstacle found is the lack of concern for some of the community towards children's education and health, both for the environment and for themselves.